Co-Development of Process Planning and Structural Configurations Considering Machine’s Accessibility in a Reconfigurable Setup - Asghar, Eram; Baqai, Aamer Ahmad; Toor, Ramshah Ahmad; Ayub, Sara (Review of Computer Engineering Research, 2016)
Manufacturing System has been evolved over the years to accommodate major design variations. To respond to these high frequency variations and to stay competitive, there is a need of having such type of manufacturing system that could cope with market trends and design changes efficiently. Product’s design and its manufacturing capabilities are closely related, thus the manufacturing system should be customized to cater all the design changes with suitable manufacturing capabilities. Reconfigurable Manufacturing system has been recommended for the turbulent market conditions because of its flexible and changeable nature. This research work is based on the co-generated model in which optimal machine configurations are generated through the application of optimization technique. Based on these configurations, system is tested for reconfiguration in case of production changeovers. Considering the relevant change drivers the degree of reconfigurability in any case of application can be achieved through proposed algorithm. A case study has been presented to illustrate the application of proposed model based on the technological constraints.